Relationship between opening and closing of stock prices for IHSG and issuers: A case study in the Indonesia Stock Exchange - Manik, Efron (Bulletin of Applied Mathematics and Mathematics Education, 2025)
Identifying the most influential variables in stock price movements is a crucial aspect of developing an accurate mathematical model for predicting market trends. This study analyzes two main variables: the composite stock price index (IHSG) and the closing price of company shares, to determine the extent of their influence on stock prices on the observation day. The findings indicate that the IHSG from one day prior to the observation day does not have a significant impact on the closing price of a particular stock. This means that changes in the IHSG on the previous day cannot be used as the main indicator to predict a company's stock price on the following day. On the other hand, the closing price of a company's stock on the previous day has a strong correlation with the company's closing stock price on the observation day, which is 70%. Besides historical stock price factors, irrational investor behavior can cause volatility that does not fully reflect a stock’s fundamental value. Therefore, it is essential to consider investors' psychological aspects in stock market analysis.